2019
DOI: 10.3390/nano9040521
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation and Characterization of Carbon Fibers with Core-Shell Structure from Graphene-Dispersed Isotropic Pitch Compounds

Abstract: In this study, isotropic pitch-based carbon fibers were prepared from a mixture of petroleum residue and graphene nanoplatelets with different contents. The softening point and synthetic yield of synthesized isotropic pitches were analyzed and compared to characterize the nature of the pitches. The surface and thermal characteristics of the fibers were observed using scanning electron microscopy and thermogravimetric analysis (TGA), respectively. From the results, it was observed that the prepared carbon fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This indicated that pre-oxidation influences the microcrystalline structures, thereby decreasing the crystallinity [ 49 ]. The d 002 value of the activated carbons (0.371 nm of PP-AC and 0.375 nm of OPP-AC) increased compared to their corresponding precursors (0.360 nm of PP and 0.363 nm of OPP) because of the disordering of the microstructures by chemical activation [ 50 , 51 ]. In addition to XRD, Raman spectroscopy was carried out to observe the microcrystalline properties of the prepared samples ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that pre-oxidation influences the microcrystalline structures, thereby decreasing the crystallinity [ 49 ]. The d 002 value of the activated carbons (0.371 nm of PP-AC and 0.375 nm of OPP-AC) increased compared to their corresponding precursors (0.360 nm of PP and 0.363 nm of OPP) because of the disordering of the microstructures by chemical activation [ 50 , 51 ]. In addition to XRD, Raman spectroscopy was carried out to observe the microcrystalline properties of the prepared samples ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…As it is applied to various fields, the demand in the market has increased widely. In addition, recently, research on using AC and ACFs as a filler for the development of high-functional polymer composite materials [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] has been steadily progressing just like carbon materials such as carbon fibers [ 50 , 51 , 52 , 53 , 54 ], carbon nanotubes [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and graphene. However, AC and ACFs have great potential to replace other carbon materials, but their potential use in polymer composite materials as reinforcing fillers has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%